The Influence of Service Quality and Price on Customer Satisfaction at Kopi Nako Bandung - Kurniawan, Ryan; Rashela, Windy; Widina (Yayasan Sinergi Kawula Muda, 2024)
This research aims to determine the influence of Service Quality and Price on Customer Satisfaction at Kopi Nako Bandung, both partially and simultaneously. Empirical study methods were used in this research, with a population taken from consumers of Kopi Nako Bandung. Data were processed using multiple linear regression analysis. The results of the correlation coefficient calculation show that Service Quality has a strong relationship with Customer Satisfaction. The results of the coefficient of determination and hypothesis testing show that Service Quality has a significant effect on the Customer Satisfaction variable. Price has a strong relationship with Customer Satisfaction. The results show that Price has a significant effect on the Customer Satisfaction variable. Meanwhile, simultaneously, it can be said that Service Quality and Price have a very strong relationship with Customer Satisfaction. Based on simultaneous hypothesis testing, there is a significant simultaneous influence between Service Quality and Price on Customer Satisfaction.